2010
DOI: 10.1002/hed.21507
|View full text |Cite
|
Sign up to set email alerts
|

Association between expression of embryonic lethal abnormal vision‐like protein HuR and cyclooxygenase‐2 in oral squamous cell carcinoma

Abstract: Our results indicate that the cytoplasmic expression of HuR is associated with COX-2 expression in OSCCs and HuR can regulate COX-2 expression in oral cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 56 publications
5
46
0
Order By: Relevance
“…Therefore, we can postulate that the elevated expression of COX2 may have an important role in predicting the clinical outcome in oral cancer, and these many essential processes in carcinogenesis make COX2 an attractive therapeutic target. In consistence with our results, Cha et al detected the expression of COX2 via immunohistochemistry analyses of 103 OSCC samples indicating that the upregulated COX2 expression in oral cell lines may be a possible prognostic parameter for reduced overall survival [19]. Similarly, Sakurai et al also found that the expression of COX2 was related to lymph node metastasis and cell proliferative activity, as well as overall 5-year survival rate in oral carcinoma, and thereby this enzyme may be valuable in diagnostic and prognostic indices in oral carcinoma [11].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, we can postulate that the elevated expression of COX2 may have an important role in predicting the clinical outcome in oral cancer, and these many essential processes in carcinogenesis make COX2 an attractive therapeutic target. In consistence with our results, Cha et al detected the expression of COX2 via immunohistochemistry analyses of 103 OSCC samples indicating that the upregulated COX2 expression in oral cell lines may be a possible prognostic parameter for reduced overall survival [19]. Similarly, Sakurai et al also found that the expression of COX2 was related to lymph node metastasis and cell proliferative activity, as well as overall 5-year survival rate in oral carcinoma, and thereby this enzyme may be valuable in diagnostic and prognostic indices in oral carcinoma [11].…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, selective COX2 inhibitors suppress growth of cells by inducing G0/G1, cell-cycle arrest, and cellular proliferation; thus apoptosis could have a reversed effect on the development and progression of cancers [17]. Similar to the results of the present study on the expression of COX2 and the pathogenesis of human tumors, previous reports have suggested a correlation between the expression of COX2 and the occurrence of oral cancer [18, 19]. In general, COX2 may initially stimulate angiogenesis and vascular endothelial cell growth that are essential in tumor growth and spread, promoting the production of prostaglandin E2 and cyclin-dependent kinase inhibitor P21 expression [20].…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Thus, cytoplasmic HuR expression can be useful as an independent prognostic parameter for the reduced overall survival of oral cancer patients. 25) Our data showed that HuR knockdown substantially lowered MMP-9 level in YD-10B cells with or without PMA stimulation, and KPS-A suppressed the cytoplasmic level of HuR peaked at 6 h after PMA exposure. These results suggest that KPS-A may reduce MMP-9 expression by blocking its HuR-mediated mRNA stabilization at the post-transcriptional level.…”
Section: Discussionsupporting
confidence: 51%
“…Four studies reported no site-specific HNC [24, 5457] and others recorded site-specific HNC. There were 7, 6 and 9 studies focused on oral cancer (OC) [22, 25, 27, 3740], laryngeal cancer (LC) [4146] and nasopharyngeal cancer (NPC) [23, 26, 4753], respectively. The total number of patients was 2430, ranging from 20 to 301 cases per study.…”
Section: Resultsmentioning
confidence: 99%